PENERIMAAN DIRI PADA MAHASISWA BROKEN HOME DI UNIVERSITAS SAHID SURAKARTA - Azzahra Anggun Salsabila; Faqih Purnomosidi; Sri Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students from broken homes are likely to experience various psychological dynamics that influence their self-acceptance. Self-acceptance is a crucial aspect of mental health, adjustment, and academic and social functioning. This study aims to explore the self-acceptance process among students from broken homes at Sahid University, Surakarta, and to identify the influencing factors and their impact on their daily lives. This study employed a qualitative approach with a case study method. The subjects were seven active students aged 18–23 from broken homes, selected using a purposive sampling technique. Data were collected through in-depth semi-structured interviews, observation, and documentation. Data validity was strengthened by triangulation of sources and methods, while data analysis employed the Miles and Huberman model. The results indicate that self-acceptance among students from broken homes is a gradual process that begins with self-awareness, followed by acceptance of the past, the development of a positive attitude toward oneself, and the ability to establish more adaptive social relationships. Internal factors such as self-understanding and emotional maturity, as well as external factors such as social support from peers and the campus environment, play an important role in shaping self-acceptance. Good self-acceptance positively impacts students' resilience, self-confidence, and academic and social adaptability.